Investigations of Pathological Immunohistochemical and Immunocytochemical Findings in Natural Infection with Mycoplasma gallisepticum in Laying Hens - Özdemir, Özgür; Yavuz, Orhan; Erer, Hüdaverdi; Sayın, Zafer (Acta Scientiae Veterinariae, 2019)
Background: Mycoplasmosis is an infectious disease caused by Mycoplasma gallisepticum (MG), usually seen in the respiratory system of chickens, chick and turkeys, that causing great economic loss. The disease is characterized by respiratory system lesions such as sinusitis, tracheitis, airsacculitis, pneumonia and other symptoms such as loss of yield, arthritis, tenosynovitis. In this study, it was aimed to investigate diagnose of the disease by pathologic and molecular techniques in hens that naturally infected with MG as well as the usability of immunocytochemical (ICC) method in diagnose of the disease. Materials, Methods & Results: For this purpose, 98 hens were collected from 10 different coops that serologically positive. After necropsy, routine pathological procedures were performed to samples taken from nose, sinus, larynx, trachea, lung and air sacs. Scraping samples taken from lungs and tracheas were evaluated by ICC. Immunohistochemical (IHC) staining was performed to samples taken from nose, sinus, larynx, trachea, lung and air sacs. Indirect immunoperoxidase method was applied in the both IHC and ICC staining. Rabbit polyclonal anti MG antibody was used as primer antibody in the IHC and ICC staining. Additionally, culture and PCR techniques were applied to tracheas of all hens for MG. The GPO3 and MGSO genes were made for PCR analysis. In the tracheal examinations, 23 cases were positive for PCR, 17 cases ICC positive, 16 cases IHC positive and 10 culture samples found positive. All of culture positive cases were also positive for other three methods. When findings in all organs were evaluated, in 37 cases were detected positive by IHC (38%) and 23 cases were positive by ICC (23.5%). In the IHC positive cases, the first order was trachea in 16 cases followed by in 11 cases in sinus, in 8 cases in lung, in 6 cases air sac and 4 cases in nose, respectively. In 8 cases, IHC positivity was found in at least two organs. IHC positivity was detected in the nose, sinus and tracheal epithelia as well as in the macrophages within subepithelial lymphoid infiltration, vascular walls and endothelium. As the disease became chronic, it was found that the agents were seen more in the lymphoid tissue than the epithelium. In ICC staining positivity was found in 17 cases in the trachea and 11 cases in the lung. There were only 5 cases positive by ICC in both organs. Discussion: Clinical and pathological findings as well as serological, microbiological, molecular techniques and immunohistochemical methods are to be important methods in the diagnosis of the disease. While the culture results are shown as the gold standard in diagnosis of the disease, it is possible to obtain the results in the earliest 7-10 days in cultures and at least 20 days must be passed in order to say a cultural negative. In addition, in the field studies, it mentioned the use of vaccines, antibiotics and protective drugs affected the results of microbiology and serology; the importance of using techniques such as IHC and PCR for the diagnosis of the causative agents. The results of the present study indicate that the most important organ in the diagnosis of the disease is the trachea, and the most effective method is PCR followed by IHC and ICC methods. It was concluded that the results of ICC staining close to IHC staining, and ICC could be used for diagnostic purposes in positive reactions obtained from the tracheas or the other organs.